Efficacy and safety of rivaroxaban in real-life patients with atrial fibrillation. (April 2015) - Barón-Esquivias, Gonzalo; Fernández-Avilés, Francisco; Atienza, Felipe; Pastor Pueyo, Pablo; Toro, Rocío; Sanmartín Fernández, Marcelo
Abstract : Rivaroxaban is a once-daily oral anticoagulant currently marketed for the prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation. This indication is largely based on the results of the ROCKET-AF trial. Although these results are robust, studies performed in clinical practice are necessary to confirm these data in real-life patients. These studies have shown rates of stroke and bleeding similar to that found in ROCKET-AF. As an anticoagulant, attention should be paid to making a correct prescription of rivaroxaban, particularly in fragile patients, to reduce the risk of bleeding. In addition, a number of studies have shown that rivaroxaban is cost-effective in clinical practice. Moreover, rivaroxaban is a good alternative to warfarin in patients undergoing elective cardioversion or atrial fibrillation ablation.